Healing fine cracks in concrete with bacterial cement for an advanced non-destructive monitoring - Kaur, Nimrat; Majhi, Subhra; Dhami, Navdeep; Mukherjee, Abhijit (Elsevier, 2020)
Cracks in concrete are inevitable and they can adversely affect the service life of structures. An efficient method to heal the cracks coupled with a reliable monitoring technique is of paramount importance. Standard crack healing materials are unable to penetrate thin cracks [1]. This paper presents an experimental demonstration of healing of fine cracks of around 0.6 mm using the bacterial based healing technique. Simultaneously, the evidence and efficiency of bacterial healing is investigated using advanced monitoring techniques. Ultrasonic signals passing through the healing area have been recorded and the waveform has been studied to interpret the condition of the crack. It has been validated through a series of water-tightness tests. The bacterial technique was able to heal the crack to the extent that no water was seen to permeate through the crack. The evidence of bacterial healing was confirmed through scanning electron microscopy and X-ray dispersion spectrum. It was found that the ultrasonic technique is able to monitor the progression of healing.